PEMBERDAYAAN KELOMPOK BIDAN EBSCO TENTANG GIZI DAN HIDRASI MELALUI APLIKASI “PERISAI BUMIL-PLUS - Erry Yudhya Mulyani; Mariyana; Nizirwan Anwar; Anindya Billa Mustika (Jurnal Abdimas Madani dan Lestari (JAMALI), 2023)
As many as 31.7% of mothers had less knowledge about nutrition and hydration and about 57.1% pregnant women were dehydrated. Currently, the use of technology as an educational medium is important to use in increasing one's knowledge. This activity is an activity in an effort to improve the knowledge, attitudes and skills of midwives in providing information to pregnant women by utilizing the educational media application "Perisai Bumil-Plus". This activity involved 171 subject midwives who are members of the EBSCO community. Conducted for 3 months (June – August 2022). The form of this activity consists of outreach activities using the lecture method, online discussions (on the network) and counseling via WhatsApp by previously providing educational media through the "Perisai Bumil-Plus" application. The socialization activity with the lecture method was carried out for 30 minutes and for approximately 60 minutes a discussion was held. Counseling activities are given to subjects who are included in the nutrition and hydration educator midwife group. This group is open for 24 hours, if there are questions, each subject has the same opportunity to ask the facilitator team. The provision of information is carried out using audio-visual media and discussions through online groups (WhatsApp). This media requires an Augmented Reality card consisting of 10 messages, which have previously been sent to midwives to be able to learn the contents of the educational message from the card. Most of the subjects in this activity had fairly good knowledge, attitudes and behavior (> 70.0%), although there were still some questions below 70.0%, namely about fluid and vitamin D needs. to provide knowledge related to nutrition and pregnancy to midwives.